The future of the past: inherent atmospheres - Hobbs, Michael Phillip (School of Architecture, Planning and Geomatics, 2018)
This dissertation is an attempt to extract architecture from the site itself. Michelangelo, the Italian Renaissance painter, sculptor, architect, poet, and engineer, famously said, Every block of stone has a statue inside it and it is the task of the sculptor to discover it. He clearly understood his role as the vessel by which an idea came to life in the physical world. In this light, the chosen site is treated much like a block of marble in the hands of a sculptor (the architect) and this dissertation is the documentation of the slow shaping, polishing, and final revealing of an idea. The design is conducted within the speculative future of the Breakwater in Cape Town Harbour. Two main interests are outlined: 1. Landscape: a desire to better understand architecture as the mediator between man and nature, essentially, and to view landscape as architecture and architecture as landscape through the dissolution of convention and the celebration of the imagination. Architectural space is treated as an extension of the site. 2. Rebirth: waste, as a by-product of contemporary consumer culture, is defined as something which no longer has value, something which is superfluous. The technological arm of this investigation is focused on the process of spatially re-imagining the breakwater site through the use de-constructed shipping vessels (machines which have become outdated and can no longer function in the post-industrial/information age). The main focus on landscape and rebirth filters through into the design of the Iziko Cape Town Maritime Museum to accurately represent the project's development from its theoretical founding to its speculative architectural resolution. Overall, this dissertation is focused on pushing the boundaries of spatial experience through the adaptation and re-imagining of a decommissioned ship. We know very well how to make good buildings which are comfortable and comply with council and environmental regulations. This endeavour is aimed at exploring new possibilities.